SlGH9-15 regulates tomato fruit cracking with hormonal and abiotic stress responsiveness cis-elements - Hao-wei LIN; Zhen WU; Rong ZHOU; Bin CHEN; Zhao-jiang ZHONG; Fang-ling JIANG (Journal of Integrative Agriculture, 2023)
Fruit cracking occurs easily during the late period of fruit development when plants encounter an unsuitable environment, dramatically affecting fruit production and marketing. This study conducted the bulked segregant RNA-Seq (BSR) to identify the key regulatory gene of fruit cracking in tomatoes. BSR-Seq analysis illustrated that two regions associated with irregularly cracking were located on chromosomes 9 and 11, containing 127 candidate genes. Further, through differentially expression analysis and qRT-PCR in cracking-susceptible and cracking-resistant genotypes, the candidate gene SlGH9-15 (Solyc09g010210) with significantly differential expression levels was screened. Bioinformatics analysis of the GH9 gene family revealed that 20 SlGH9 genes were divided into three groups. The phylogenetic analysis showed that SlGH9-15 was closely related to cell wall construction-associated genes AtGH9B1, AtGH9B6, OsGH9B1, and OsGH9B3. The cis-acting elements analysis revealed that SlGH9-15 was activated by various hormones (ethylene and ABA) and abiotic stresses. The expression pattern indicated that 13 SlGH9 genes, especially SlGH9-15, were highly expressed in the cracking-susceptible genotype. Its expression level gradually increased during fruit development and achieved maximum value at the red ripe stage. Additionally, the cracking-susceptible tomato showed higher cellulase activity and lower cellulose content than the cracking-resistant tomato, particularly at the red ripe stage. This study identified SlGH9-15 as a key gene associated with fruit cracking in tomatoes for the first time and gives new insights for understanding the molecular mechanism and complex regulatory network of fruit cracking.